2012
DOI: 10.1007/s00246-012-0375-8
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Extremely Preterm Infants (<1,000 g) With Congenital Heart Defects From the National Institute of Child Health and Human Development Neonatal Research Network

Abstract: Little is known about the outcomes of extremely low birth weight (ELBW) preterm infants with congenital heart defects (CHDs). The aim of this study was to assess the mortality, morbidity, and early childhood outcomes of ELBW infants with isolated CHD compared with infants with no congenital defects. Participants were 401–1,000 g infants cared for at National Institute of Child Health and Human Development Neonatal Research Network centers between January 1, 1998 and December 31, 2005. Neonatal morbidities and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 25 publications
3
38
1
Order By: Relevance
“…Major CHD was more common in our cohort of VLBW infants compared with the general population, but lower than in prior VLBW studies [2,6,7]. The overall proportion of VLBW infants with major CHD in our cohort was 299/105,539 (0.3%) and remained unchanged for the duration of the study.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Major CHD was more common in our cohort of VLBW infants compared with the general population, but lower than in prior VLBW studies [2,6,7]. The overall proportion of VLBW infants with major CHD in our cohort was 299/105,539 (0.3%) and remained unchanged for the duration of the study.…”
Section: Discussioncontrasting
confidence: 55%
“…Mortality in VLBW infants with major CHD is high, but previous studies were limited by inclusion of infants with isolated atrial septal defect (ASD) or ventricular septal defect (VSD), missing information on neonatal morbidities, or inability to examine trends in mortality over time [2,6,7]. The pathophysiologic mechanisms responsible for higher mortality of VLBW infants with congenital heart defects are unknown, but comorbidities associated with the need for surgical intervention and prolonged hospitalization likely play a significant role.…”
Section: Introductionmentioning
confidence: 99%
“…41,42 Poor fetal growth increases the morbidity and mortality of infants with BDs. 43 The outcomes and survival of infants with CHDs is significantly worse for those born preterm, particularly at earlier gestational ages. 43 The neonatal course and long-term outcomes of infants with BDs requiring surgeries and lengthy hospitalizations are complicated by low birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…43 The outcomes and survival of infants with CHDs is significantly worse for those born preterm, particularly at earlier gestational ages. 43 The neonatal course and long-term outcomes of infants with BDs requiring surgeries and lengthy hospitalizations are complicated by low birth weight. At 18 to 22 months' corrected age, infants with extremely low birth weight and congenital anomalies are at a significantly higher risk of poor growth, requiring in-hospital care and neurodevelopmental impairment than those extremely low birth weight infants without anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Management of these infants is challenging due to neonatal comorbidities such as BPD, and inability to intervene surgically due to small size. Pappas et al 22 reported an increased risk of growth impairment and neurodevelopmental impairment among ELBW survivors with congenital heart defects. It will be important to monitor mortality trends in VLBW infants with congenital heart defects over time and morbidity among survivors.…”
Section: Types Of Birth Defectsmentioning
confidence: 99%